2015
DOI: 10.1380/ejssnt.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport Properties of Graphene Channel between Au Electrodes

Abstract: We study the electronic transport properties of armchair graphene nanoribbons with a width of up to 12 nm bridged between two Au electrodes using first-principles calculations. The transport properties sensitively depend on the ribbon width, even though the width reaches 12 nm. The variation of transport properties is ascribed to the detailed electronic structures of graphene ribbons, which sensitively depend on their width. The band structure and the symmetry of π state of the graphene play important roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We performed electron transport calculations by means of the NEGF extension of the OpenMX code, 29 which is by now widely used. [38][39][40][41][42][43] The model implemented in this software makes use of periodic boundary conditions. The basis sets employed consist of linear combinations of atomic orbitals generated by a confinement scheme which yields wave functions with zero value beyond a chosen cutoff radius.…”
Section: Methodsmentioning
confidence: 99%
“…We performed electron transport calculations by means of the NEGF extension of the OpenMX code, 29 which is by now widely used. [38][39][40][41][42][43] The model implemented in this software makes use of periodic boundary conditions. The basis sets employed consist of linear combinations of atomic orbitals generated by a confinement scheme which yields wave functions with zero value beyond a chosen cutoff radius.…”
Section: Methodsmentioning
confidence: 99%
“…The symmetry of the p state of the AGNRs also contributes to reduce the currents with the Au electrodes. 14 We have found that the currents in the AGNR-Ti contact are over 10 times as great as those in the AGNR-Au contact, even though the AGNR width reaches 12 nm. Nevertheless, the experiment has reported that the Ti contact results in higher contact resistance values (R c ¼ 48.0 6 5.7 kX lm) compared to the Au contact (R c ¼ 3.9 6 1.5 kX lm).…”
Section: B Transport Propertiesmentioning
confidence: 73%
“…The high carrier mobility allows the material to be applied to the high-speed electronic devices in the post-silicon era. On the other hand, the electronic properties of graphene are significantly fragile against the surrounding foreign materials, such as metal electrodes [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and insulating substrates. [15][16][17][18][19][20][21][22][23][24][25][26] This is because the whole area of graphene intrinsically forms interfaces with such foreign materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations